Meningkatkan Hasil Belajar Siswa Tentang Perkembangan dan Pertumbuhan Manusia melalui Metode Inkuiri Terbimbing - Nurul Suhariningsih (Jurnal Kreatif Online, 2021)
The purpose of this study was to improve learning outcomes and mastery of material in science learning on human development and growth through guided inquiry methods. The research subjects were students of class VI with a total of 30 students consisting of 11 boys and 19 girls. This type of research used classroom action research which was carried out in 2 cycles. Each cycle consists of 4 stages, namely planning, implementing, observing and reflecting. Qualitative data from observations of the learning process were analyzed using quantitative descriptive analysis by comparing cycle I to cycle II, while data in the form of data from student learning outcomes was analyzed by comparing the initial condition, cycle I and cycle II test scores, and reflection. The results showed that the implementation of the guided inquiry method could improve activities and science learning outcomes about development and growth for grade VI students at SDN Lampasio in 2019. Teaching and learning activities of students from initial conditions to final conditions have increased, from cycle I the average value was 71, while in cycle II the average value was 83.